Analysis The Effect of Effectiveness and Trust in Use Accounting Information System Technology on Individual Performance of Cooperative Employee in Purwokerto - Nugroho, Fajar Setyo (Business, Accounting and Management Journal, 2023)
This research is titled “Analysis of The Effect of Effectiveness and Trust in Use Accounting Information System Technology on Individual Performance of Cooperative Employees in Purwokerto”. This study aims to determine the effectiveness and trust of using accounting information systems on individual employee performance at cooperatives in Purwokerto. The data collection method conducted in this study is a survey method with a questionnaire. This research was conducted at cooperatives in Purwokerto. The dependent variable of this study is individual employee performance, and the independent variables are the effectiveness of the use of accounting information system technology and trust in the use of accounting information system technology. The sampling technique uses a purposive sampling technique, while the analytical method is a multiple linear regression method. The sample in this study amounted to 60, and the research method used was quantitative research. The variable effectiveness of the use of accounting information system technology has a significant positive effect on individual employee performance and variable trust in the use of accounting information system technology has a significant positive effect on individual employee performance. Cooperatives are expected to update the existing accounting information system so that the system will always follow the development and needs of employees. In addition, cooperatives must conduct special training for employees in operating a new system if there is new technology. This is important because of information system technology has a large and positive effect on the effectiveness and productivity of employee task completion.